Doctor Faustus - Marlowe, Christopher (Pearson Education Ltd, 1995)
Weary of academic study, an eminent scholar turns to magic and makes a deal with the Devil. Mephostophilis will serve him and give him whatever he wants. But after twenty-four years, Faustus must keep his side of the bargain$1! =s
Keywords: Juvenile Literature; Plays